Independent Learning Curriculum Policies and Challenges in Building Children's Character - Rahayu, Sri; Wahid, Abd Hamid; Zahro, Maulidatun Nafizatuz (JURNAL AL-TANZIM, 2023)
This study aims to analyze the independent learning curriculum policy and its challenges in building children's character. This research was conducted at SMA Nurul Jadid Paiton Probolinggo with a qualitative phenomenological-naturalistic approach. Data was obtained from observation, interviews and documentation. Research data analysis was carried out in stages, starting with collecting, reducing, presenting, and concluding the findings. The study results show that the independent curriculum policy is carried out by analyzing the internal and external environment, networking and building an independent attitude. While the challenges of curriculum policy in building children's character consist of; class ranking, learning internalization principles and technological sophistication. This research contributes to the importance of redesigning local wisdom-based learning curricula so that they can produce good children's character.